Reappraisal of the genetic diversity and pharmacogenetic assessment of CES1. (August 2017) - Ferrero-Miliani, Laura; Bjerre, Ditte; Stage, Claus; Madsen, Majbritt Busk; Jűrgens, Gesche; Dalhoff, Kim Peder; , INDICES; Rasmussen, Henrik Berg
The CES1 gene encodes a hydrolase that metabolizes important drugs. Variants generated by exchange of segments with CES1P1 complicate genotyping of CES1. Using a highly specific procedure we examined DNA samples from 200 Caucasians and identified 46 single nucleotide variants (SNVs) in CES1 and 21 SNVs in CES1A2, a hybrid composed of CES1 and CES1P1 . Several of these SNVs were novel. The frequencies of SNVs with a potential functional impact were below 0.02 suggesting limited pharmacogenetic potential for CES1 genotyping. In silico PCR revealed that the majority of the primer pairs for amplification of CES1 or CES1A2 in three previous studies lacked specificity, which partially explains a limited overlap with our findings.